Efficacy and safety of acupuncture in treating post-traumatic stress disorder: A protocol for systematic review and meta-analysis. Issue 26 (26th June 2020) - Ding, Ning; Li, Linzhi; Song, Kai; Huang, Ailing; Zhang, Hong
Abstract: Background: Post-traumatic stress disorder (PTSD) acts as a complex mental illness in which individuals are prone to long-lasting mental disorders after suffering traumatic events. PTSD is usually accompanied by some comorbidities, such as depressive disorder and sleep disorder, which seriously threaten patients' life and health. Evidences showed that acupuncture could remarkably relieve the symptoms of PTSD patients. The review aims at assessing the safety and effectiveness exhibited by acupuncture for treating PTSD patients. Methods and analysis: The literature identified by searching 8 English electronic databases and 5 Chinese electronic databases from their inception to April 20, 2020 will be incorporated into the study. Two researchers will independently take charge of the research selection, the data extraction, as well as the assessment on research quality. The primary outcomes will be total PTSD symptoms, measured by different instruments including interviews and self-report measures. Data analysis will be performed via the RevMan 5 software, and Grading of Recommendations Assessment, Development, and Evaluation will help to assess the evidence level. A heterogeneity x 2 test, the Higgins' I 2 test as well as visually inspecting the forest plot will help to investigate the heterogeneity of data. A sensitivity analysis and subgroup analyses will assist in investigating the sources of heterogeneity. Ethics and dissemination: The review neither assesses the individual information of patients nor impacts their rights, so it is not necessary for it to be approved by ethical institution. The article will be published in a peer-reviewed journal and present at relevant conferences. OSF registration number: https://osf.io/dc3js .